Study of Chlorophyl-A Variability in Bone Bay Waters During High Wave Events - Musgamy, Hijrah K.; Jasruddin, Jasruddin; Palloan, Pariabti (Advances In Social Humanities Research, 2024)
Research has been carried out on the distribution of chlorophyll-a in the waters of Bone Bay during high wave events based on the parameters of sea surface temperature, wind speed and ocean currents. The aim of this research is to analyze parameters related to high waves which influence chlorophyll-a concentrations in the waters of Bone Bay. Chlorophyll-a patterns in Bone Bay waters were studied based on Aqua MODIS satellite data for chlorophyll-a data and ECMWF for wind speed, sea surface temperature and ocean current data. The average value was determined using Aqua MODIS and ECMWF satellite data for 10 years from 2011 to 2020. These parameters were analyzed to determine the correlation with chlorophyll-a. The calculation results show that sea surface temperature and wind speed decreased after high waves, while ocean currents and chlorophyll-a increased after high waves in Bone Bay waters. The correlation between chlorophyll-a and wind speed is 0.15, with sea surface temperature -0.44, and with ocean currents -0.26. Spatially, high concentrations of chlorophyll-a are found in the coastal waters of the South Sulawesi region with chlorophyll-a concentrations reaching 0.4-5 mg/m3. Temporally, high chlorophyll-a concentrations occur after high wave events with an average chlorophyll-a concentration of 0.32 mg/m3.